Development and Evaluation of Culturally-Competent Cookies Supplemented with Locally Grown Crops in Uttarakhand - Dhami, Pushpa; Jain, Shruti; Bains, Kiran; Kaur, Harpreet (Indian Journal of Extension Education, 2020)
Present study was aimed to develop and assess the acceptability of culturally-competent cookies based on locally grown crops for the vulnerable population of a disaster-prone Himalayan state Uttarakhand. The supplemented cookies were developed using a cereal-pulse-millet mix of wheat flour, black soybean or Bhat flour and ragi or Madua flour in the ratio of 60:20:20 and were found to be high in protein (18.58%), fat (20.09%), fibre (1.67%), ash (2.53%), lysine (585.2 mg), NDP Cal % (13.4%), calcium (97.2 mg), iron (4.9 mg) and zinc (0.88 mg). These were acceptable for 60 days in aluminum laminate pouches. A consumer acceptability trial to determine the acceptability of these cookies by the local population showed a significantly (pdâ€0.01) higher acceptability by all age groups. It was concluded that cookies were nutrient dense food which can be effectively targeted for meeting the nutritional needs of the disaster hit population and address the food insecurity issues that arise aftermath any emergency especially when the donated food conflicts with the cultural/religious beliefs of the affected region.